Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1017/s0269964808000119
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the Throughput of Tandem Lines With Flexible Failure-Prone Servers and Finite Buffers

Abstract: Consider a tandem queueing network with an infinite supply of jobs in front of the first station, infinite room for completed jobs after the last station, finite buffers between stations, and a number of flexible servers who are subject to failures. We study the dynamic assignment of servers to stations with the goal of maximizing the long-run average throughput. Our main conclusion is that the presence of server failures does not have a major impact on the optimal assignment of servers to stations for the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Hence, the threshold for server 2 (the state where server 2 starts working at station 2) is either 1 or 2 in both cases, but the value of the threshold may be different in Markovian and deterministic systems (e.g., for the system with µ 11 = µ 32 = 2, µ 12 = µ 22 = 1, µ 21 = 0.5, and µ 31 = 0.1, we have r 0.94 and r M 1.08). This is consistent with the results of Andradóttir et al [10] for Markovian systems with server failures, where the optimal policy was found to be of threshold type (as for systems without server failures), with the value of the threshold depending on the server failures. Together these results suggest that the optimality of the threshold policy of Andradóttir and Ayhan [5] is quite robust to the assumptions it is derived under, but the value of the threshold must be determined using the parameters of the problem at hand.…”
Section: General Service Timessupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, the threshold for server 2 (the state where server 2 starts working at station 2) is either 1 or 2 in both cases, but the value of the threshold may be different in Markovian and deterministic systems (e.g., for the system with µ 11 = µ 32 = 2, µ 12 = µ 22 = 1, µ 21 = 0.5, and µ 31 = 0.1, we have r 0.94 and r M 1.08). This is consistent with the results of Andradóttir et al [10] for Markovian systems with server failures, where the optimal policy was found to be of threshold type (as for systems without server failures), with the value of the threshold depending on the server failures. Together these results suggest that the optimality of the threshold policy of Andradóttir and Ayhan [5] is quite robust to the assumptions it is derived under, but the value of the threshold must be determined using the parameters of the problem at hand.…”
Section: General Service Timessupporting
confidence: 91%
“…Andradóttir and Ayhan [5] characterized the optimal server assignment policy for Markovian systems with two stations and more than two flexible servers, and Andradóttir et al [10] considered the effects of server failures in the same settings.…”
Section: Introductionmentioning
confidence: 99%
“…They provided heuristic, round-robin policies to maximize the throughput. Andradóttir, Ayhan and Down [2] considered a tandem queueing network with unreliable servers and showed that server unreliability does not change the structure of the optimal policy in some specific cases. They first considered a tandem queue with arbitrary numbers of stations and unreliable servers (which are generalists).…”
Section: Introductionmentioning
confidence: 99%
“…service times. The result is extended in [7] to include networks with failure-prone servers. Clearly, any tandem network with only one server satisfies the "generalist" condition.…”
Section: Introductionmentioning
confidence: 99%
“…Sennott et al [15] analyze tandem production lines with multiple servers, dedicated servers The work most closely related to this paper involve maximizing throughput in tandem queues. Apart from [2] and [3] which are described in detail above, Andradottir et al also investigated tandem lines with flexible and dedicated servers [6], failure prone servers [7], and synergistic servers [8]. Kirkizlar et al [12] analyze a tandem production line which is understaffed, i.e., there are more stations than servers.…”
Section: Introductionmentioning
confidence: 99%